Optimizing efficiency and sustainability in higher education: development and validation of a lean thinking adoption instrument - Avilés-Noles, Andrés; Guevara-Viejó, Fabricio; Fajardo Aguilar, Pedro Javier; Rueda-Varón, Milton Januario; Velosa García, José Divitt (Frontiers in Education, 2025)
IntroductionLean Thinking has been applied across various sectors to optimize processes and improve efficiency; however, its implementation in higher education still faces methodological and structural challenges.MethodsThis study developed and validated an instrument to measure the application of Lean Thinking in Ecuadorian higher education institutions. A cross-sectional empirical design was used, involving 315 university students who responded to a 42-item questionnaire. Data were analyzed through exploratory and confirmatory factor analyses.ResultsThe results revealed an eight-dimensional factorial structure addressing leadership, long-term thinking, continuous improvement, waste elimination, student value, teaching, research, and community engagement. The instrument showed high reliability (Cronbach’s α = 0.94; factor loadings > 0.40), convergent validity (AVE > 0.40), and discriminant validity (HTMT < 0.85). Model fit indices confirmed its robustness (CFI = 1.000, TLI = 1.008, RMSEA = 0.000). Leadership was the highest-rated factor (M = 7.53, SD = 1.09), while research scored the lowest (M = 7.25, SD = 1.13).DiscussionThis validated tool provides a reliable means to assess Lean adoption in higher education. Findings suggest that Lean implementation enhances institutional efficiency and student experience, though sustained impact requires long-term strategies.